STATISTICAL SIMULATION FOR INFLUENCE OF WOOD CHARACTERISTICS ON PROPAGATION SPEED OF ULTRASONIC WAVES - Storozhyk, Oleksandr; Sokolowskyy , Yaroslav (Forestry, Forest, Paper and Woodworking Industry, 2009)
The statistical simulation for propagation speed of ultrasonic waves in wood is presented in the article. The regression dependences for propagation speed of ultrasonic waves on physical characteristics of wood are obtained. The rotatable second order plan is used for statistical simulation.